Modelling the long-term impacts of atmospheric pollution deposition and repeated forestry cycles on stream water chemistry for a holm oak forest in northeastern - Neal, C; Avila, a; Rodà, F (Journal of Hydrology, 1995)
Estimates based on the MAGIC model of the long-term effects on stream water quality of forest management cycles as well as of atmospheric pollutant inputs for a holm oak catchment in northeastern Spain, show that despite high pollutant sulphur inputs as well as substantial base cation loss from the catchment owing to forest harvesting, stream water has not deteriorated in any major way. Acidification of the catchment will continue, to a limited degree, unless either sulphur deposition is reduced by more than 60% or forest harvesting schemes are terminated. The detrimental changes in water quality owing to acid deposition and forestry harvesting practice in other parts of Europe are not observed in this region, because of high base inputs from the atmosphere and high base cation weathering rates within the catchment.
Keywords: atmospheric deposition; forestry practices (voyant); pollution; soil chemistry; stream water chemistry

Soilwater chemistry in a holm oak ( Quercus ilex) forest: inferences on biogeochemical processes for a montane-Mediterranean area - Avila, Anna; Bonilla, David; Rodà, F; Piñol, J; Neal, C (Journal of Hydrology, 1995)
Soil solution and free-flowing soilwater were sampled at various depths for 3 years in a plot of holm oak (Quercus ilex L.) in the Montseny mountains (NE Spain). The soil solution retained at -65M kPa in the mineral soil at depths of 20 and 40 cm had a different chemistry from that of throughflow under the humic layer (H-layer throughflow) and, to a lesser extent, from deep subsurface flow. The dominant mobile anion in the soil solution and the deep flow was SO:-, whereas in the H-layer, SOi- was overridden by alkalinity. H-Layer throughflow chemistry was extremely variable, in consequence of the large number of biogeochemical processes affecting it (e.g. rainfall chemistry, dry deposition, leaching from canopy and litter, decomposition), and of the quantity of water available for transport of solutes. The chemistry of the soil solution was more predictable, as it was governed mainly by nutrient uptake, cation exchange reactions and the seasonal wetting and drying cycles. The chemistry of the deep subsurface flow was often intermediate between that of the soil solution and that of the H-layer throughflow; this suggested a mixture of displaced pre-event soil solution and of H-layer throughflow circulating through preferential flow paths. With humid antecedent conditions, the chemistry of the deep subsurface flow approached that of the soil solution. The cation concentration relationships in the soil solution were strongly linear. In a homogeneous soil, cation exchange theory predicts this to be expected only for cations of the same charge, whereas cations of different charges should follow power relationships. Our results, however, are consistent with a theoretical approach involving cation exchange reactions in a highly heterogeneous environment. Indeed, our study illustrates the heterogeneous nature of the soils, as the power relationship has been obscured completely. Soilwater chemistries were markedly different from those of streamwater, particularly under dry conditions. During baseflow, the stream is fed by groundwater, and the soils are probably disconnected from the stream. During humid periods, the chemistry of the streamwater tends toward that of the deep subsurface flow. Chemical hydrograph separation indicates that, on average, stormflow water comprises an approximately one to one mixture of groundwater and deep subsurface flow.
Keywords: biogeochemistry; chemical composition; forest soils (citation); Ions; Soil depth; soil pH; soil water; temporal variation

Stable hydrogen and oxygen isotope studies of rainfall and streamwaters for two contrasting holm oak areas of Catalonia, northeastern Spain - Neal, C; Neal, M; Warrington, Anita; Avila, a (Journal of Hydrology, 1992)
Results are presented of a study of stable hydrogen and oxygen isotopes in rainfall and streamwaters for the Montseny and Prades areas in northeastern Spain: results cover the full year of 1991. The isotopic pattern for rainfall is similar for both areas: there is a wide range in isotopic contents and the results show a strong, near-linear trend, 62H = 7.9 x 6~80 + 9.8 (N = 59; r 2 = 0.952), the 'local meteoric line'. There is slight curvature to the data which may be related to the sources of water vapour forming the rainfall. Within the streams, the isotopic variability is much less than that of the rainfall although the data lie on, or very near to, the meteoric line. Data for detailed collections during storm events show more scatter than those collected regularly on a fortnightly basis. The event data show a linear feature that conforms to the local meteoric line. These results indicate that: (1) the main supply of water to the stream stormflow comes from water stored in the catchment prior to the event; (2) waters of more than one isotopic composition reside within the catchment and are transferable to the stream during storm events; (3) the main process of water transfer from the catchment back to the atmosphere comes from transpiration by the trees and (possibly) complete evaporation from the near-surface soil horizons and the tree canopy; (4) the isotopic technique cannot be used for quantitative hydrograph separation in this instance at least two water types can be present within the catchment at any given time.
Keywords: isotope composition (voyant); RAINFALL; stream water